Effets D’un Programme D’entrainement De 8 Semaines Chez Des Femmes Infectees Du Vih Sous Traitement Antiretroviral (Arv) En Cote d’Ivoire - N’guessan, Kouamé; Madani, Coulibaly Sarigalo; Siaka, Coulibaly; Andrée Joelle, Kaffet Sylvie; Antoine, Tako Némé (European Scientific Journal, ESJ, 2016)
Objective: To evaluate the effects of 8-week specific Fitness training program on the physical, mental and immunological health of women infected by the virus of the human immunodeficiency and on antiretroviral treatment (ARVT). Methods: a program of sixteen sessions of specific Fitness training displayed over 2 months with two sessions of one hour a week was realized in 48 physically inactive women from 25 to 52 years old, living with the HIV and under antiretroviral treatment. The physical health of the women was evaluated before and after two months of training through body mass index, muscular strength, recovery from exhaustive exercise capacity, flexibility, general balance, immunological state, self-confidence, and self-esteem. The effects of specific fitness training on these parameters were examined through statistical tests of comparison (student t test, paired sample and frequencies). Results: the results of sixteen sessions of training show a significant improvement (p˂0,05) on the general health through the corpulence, the muscular strength, the recuperative capacity, the flexibility, the general balance, the immunological state, the self-confidence, and the self-respect. Conclusion: the implication in the practice of physical activities contributes to improve the health, the quality of life of the PVVIH and the image that they have of themselves, so favoring an acceptance of their own situation and reducing the exclusion, the discrimination and the stigmatization of which they feel victims.